TWO-VARIATE ANALYSIS. - Watson, Robert H. (The Accounting Review, 1960)
Abstract In most works on cost accounting the topic of variance analysis is handled by multiplying the current value of one variate by the change in the other variate, subtracting this product from the total variance, and then attributing the difference to the second variate. Two-variate analysis is appropriate when any two factors are multiplied to produce a result. Variance in gross profit from one period to another is the change in net sales minus the change in the cost of goods sold. The sales are composed of units sold multiplied by prices per unit. The variance in sales may be subjected to two-variate analysis; so may the variance in the cost of goods sold. When a laborer's performance is compared with predetermined standards, his variance from a predetermined standard may be attributed to the hours worked and the efficiency with which he performs. In any consideration of the economics of price, the two basic variates are the unit price and the quantity. However, the quantity may be correlated with advertising outlay, selling effort, sums spent on product research, or any other desired variate.